Amyloidosis History and Perspectives - Harrison, Jonathan S. (IntechOpen, 2022)
This volume presents a comprehensive overview of amyloidosis, beginning with a general historical overview and proceeding to a discussion of the subtypes of amyloidosis encountered in clinical medicine. The unifying feature common to all amyloidoses, that of misfolded proteins, is explored in some detail, and the pathobiology and manifestations are delineated for major disease entities. Both inherited and acquired amyloidosis are examined, and a discussion of current treatment approaches are included for many of these subsets. It is hoped that the volume will be useful to readers who approach the topic from a wide variety of disciplines.